Myelodysplastic Syndrome With Trisomy 8 and Behçet Disease‐Like Intestinal and Upper Gastrointestinal Involvement - Kawata, Yuzo; Tominaga, Kentaro; Kaneko, Yusuke; Takashima, Saori; Tani, Yusuke; Kojima, Yuichi; Takahashi, Kazuya; Terai, Shuji (Clinical case reports, 2025)
We found an extremely rare case of upper gastrointestinal involvement in trisomy 8‐positive myelodysplastic syndrome. This is the first reported case of trisomy 8‐positive myelodysplastic syndrome with both upper and lower gastrointestinal involvement, which was successfully treated with bone marrow transplantation.